Nouvelles crepidogaster (Coleoptera, Caraboidea, Brachinidae) d’Afrique occidentale et de Madagascar - Deuve, Th. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2005)
Four new species are described within the genus Crepidogaster Boheman, 1848: C. amieti Deuve, sp. n. from Cameroon, C. dolini Deuve, sp. n., C. kavanaughi Deuve, sp. n. and C. mateui Deuve, sp. n. from Madagascar. An identification key is given for all the Crepidogastrinae species known from Madagascar.